Transformasi Ekonomi melalui Pendekatan Akhlaq dan Hukum Islam: Ekonomi, Akhlaq dan Hukum Islam - Budianto, Tenda; Zamzami, Zamzami; NaufalFalih, Imam (Tasyri' : Jurnal Muamalah dan Ekonomi Syariah, 2024)
The transformation of the economy through the approach of Islamic ethics and law has been a central focus in contemporary economic discourse. This research explores the impacts of incorporating moral values and principles of Islamic law in reshaping economic paradigms. This approach emphasizes the importance of justice, transparency, and social responsibility within the economic system. In-depth analysis of Islamic economic concepts reveals the potential to address economic inequalities and promote sustainable development. Furthermore, the application of Islamic ethics and law can provide an ethical foundation for responsible and sustainable business practices. The findings suggest that sustainable economic transformation requires the integration of Islamic values with modern economic practices. Relevant policy implications are also discussed to support the implementation of these concepts within the current global economic context. Keywords : Economic Transformation, Islamic Ethics, Islamic Law, Economic Justice, Sustainable Development.